Feature Binding of Sequentially Presented Stimuli in Visual Working Memory - Bharti, Anuj Kumar; Yadav, Sandeep Kumar; Jaswal, Snehlata (Frontiers in Psychology, 2020)
Feature binding is a process that creates an integrated representation of an object. A change detection task with four stimuli is used to study colour-shape binding of sequentially presented stimuli. Given the immense importance of locations in feature binding, and noting the confound of location information with simultaneous presentation, we compared simultaneous and sequential presentation when locations remained the same from study to test and when they changed randomly. In Experiment 1, sequential presentation implied showing the stimuli one by one to gradually build up the study display. There were no differences between the two modes of presentation in this experiment, although performance was better with unchanged locations than random locations. Experiment 2 used a sequential presentation when one stimulus vanished as the next was presented. An interaction effect showed that performance was much better with unchanged locations than random locations with simultaneous presentation, whereas locations had no effect in the sequential presentation condition. Three subsequent experiments, with drastically reduced presentation time for the display in the simultaneous presentation condition (Experiment 3), with blank intervals inserted after every stimulus in the sequential presentation condition (Experiment 4), and with a mask given immediately after the study-display presentation (Experiment 5), showed results similar to Experiment 2. Thus, we surmise that locations are a factor only in simultaneous presentation, and not in sequential presentation, and the differences between the two conditions can be attributed to post-perceptual factors within visual working memory.